A descontextualização do objecto na arte - Moreira, Daniel Arnaut, 1986- (2014)
This thesis, based on the works of Marcel Duchamp and Jeff Koons, begins with the analyses of the decontextualization of the art object. This goal, driven by the book O Humor e a Lógica dos Objectos de Duchamp, by José Gil e Ana Godinho, leads us to create a relation between religious objects, common in modern religions, and fetich or totems, common in the so-called “primitive” societies. This analogy has its basis on the work of Alfred Gell, an anthropologist that defends that art was sacralized, and that contemporary artists can be compared to the shamans and clerics of ancient times. This thesis concludes, based on the work of Gell, that the role of the object in society, at a symbolic level, works as an index. The decontextualization of the object, besides changing his function, is also going to change its meaning. It is the construction of new meanings, through the manipulation of context, that artists like Duchamp and Koons rely on. The similarity between an object of art and an object of religious cult, is not only a product of its indexing nature – between man and object – but essentially, how art and religion are structured in society